1 - Ou en est la «théorie du développement» ? - Fayçal YACHIR, (Africa Development, 1985)
Development theory, as imposed in the 1950s as a discipline in the dominant economics, has very little theoretical basis. A. HIRSCHMAN defines development theory as a negation of the principle of mono-economics — (a negation which implies that under developed countries are endowed with a number of common features which distinguish them clearly from advanced industrialized countries, and thus could not be studied without seriously changing, in a number of important areas, admitted facts in the conventional economic analysis which is oriented toward industrialized countries). As a result the point of departure of economists who are involved in the study of Third World economies is the observation of specific phenomena which are inexistent in the Western economy. These observed phenomena, however are mere descriptions as no explanation is given as to their origins, or their significance. The common practice which consists of singling out specific phe nomena, among others, to establish the specificity of the situation of Third World countries therefore reveals itself to be totally arbitrary — In effect, this results in priviledging an aspect of a complex reality about which these economists lack a total comprehension. Furthermore, the development economists, by so proceeding, are not really attempting to produce new knowledge or theories on development/under-development, but simply trying to identify the exceptions to conventional analysis. HIRSCHMAN points out that the blow that KEYNES dealt to the principle of mono-economics led to the immediate acceptance of the concept of a third type of economic science. To be sure, the blow dealt by KEYNES to neo-classical orthodoxy made it easier for Western academia and government circles to accept a non-orthodox «economics of develop ment» but this was not at all a third type of economics, furthermore it did not displace the others. Development economists did not develop a new approach, they simply dove into the stock of the dominant economics for tools which to them appeared more relevant to the new reality discovered. The novelty of development economics is mostly due to attempts at replacing the neo classical orthodoxy by Keynesian and conventional tools with a view to grasping phenomena which are said to be specific but whose genesis or nature is nowhere questioned.